Pelatihan Inovasi Permen Soba Rumput Laut Untuk Pemberdayaan Ekonomi Masyarakat - Sahami, Femy M.; Kalaka , Sri Rahayu; Nursinar, Sitti; Djunaidi, Sandrianto (JURNAL PENGABDIAN PAPUA, 2025)
The training on seaweed-based soba candy innovation in Keramat Village, Gorontalo Regency, aims to empower the local community by enhancing their knowledge and skills in processing seaweed into high-value food products. Designed to address the abundant local seaweed resources, the program sought to create innovative candy products that are not only nutritious but also economically promising. This activity resulted in an 88% increase in participants' knowledge and a 71% improvement in technical skills, demonstrating the training's effectiveness. Participants included members of the Family Welfare Movement (PKK) and micro, small, and medium-sized enterprise (MSME) actors, who engaged in interactive sessions combining lectures, discussions, and hands-on practice. The seaweed-based soba candy innovation has significant potential to contribute to community economic empowerment by utilizing simple yet innovative processing methods. However, challenges remain in creating attractive packaging and adopting digital marketing strategies to expand market reach. Overall, this training supports the development of sustainable local industries and promotes the introduction of healthy snacks made from natural ingredients.